2021
DOI: 10.3389/feart.2021.652501
|View full text |Cite
|
Sign up to set email alerts
|

Neodymium Isotopes in Glauconite for Palaeoceanographic Reconstructions at Continental Margins: A Preliminary Investigation From Demerara Rise

Abstract: Contourite sediment accumulations at continental margins are related to strong bottom water circulation, where intense winnowing can result in neoformation of authigenic grains of glauconite at the seafloor. In this study, we investigated whether such glauconite grains could faithfully record ambient bottom-water neodymium (Nd) isotopic compositions, and hence be used as paleoceanographic archives. To this purpose, we measured Nd isotopic compositions (εNd) in a series of glauconitic grains, foraminiferal asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Previous work [Amorosi andCentineo, 2000, Tribovillard et al, 2021] showed that the glauconite of the Boulonnais chalk responded to the typical logic of formation: very slow sedimentation rate in the "Chalk Sea" in connection with the great transgression of the Upper Cretaceous, prolonged exchanges with seawater at the sediment-water interface, formation of a synsedimentary glauconite rich in iron and potassium, showing relatively large grains and an absence of particle size sorting. The long duration of the exchanges between the seawater and the sediment-water interface could have been caused by the reduced flux of particles or by winnowing induced by currents affecting the seabed [Giresse, 1985, Giresse et al, 2021, see the works of and references therein]. In contrast, the glauconite of the Aptian-Albian sandstones and that of most of the Jurassic deposits studied here show smaller, well sorted grains, which are therefore not synsedimentary but reworked from their source zones.…”
Section: Synsedimentary Versus Reworked Glauconitementioning
confidence: 95%
“…Previous work [Amorosi andCentineo, 2000, Tribovillard et al, 2021] showed that the glauconite of the Boulonnais chalk responded to the typical logic of formation: very slow sedimentation rate in the "Chalk Sea" in connection with the great transgression of the Upper Cretaceous, prolonged exchanges with seawater at the sediment-water interface, formation of a synsedimentary glauconite rich in iron and potassium, showing relatively large grains and an absence of particle size sorting. The long duration of the exchanges between the seawater and the sediment-water interface could have been caused by the reduced flux of particles or by winnowing induced by currents affecting the seabed [Giresse, 1985, Giresse et al, 2021, see the works of and references therein]. In contrast, the glauconite of the Aptian-Albian sandstones and that of most of the Jurassic deposits studied here show smaller, well sorted grains, which are therefore not synsedimentary but reworked from their source zones.…”
Section: Synsedimentary Versus Reworked Glauconitementioning
confidence: 95%
“…The temperatures reported for glauconitization from low-latitude sea bottoms of the continental shelf are generally about or slightly below 15 • C. For the first time, glauconitization proceedings were documented near 3 • C at water depths beyond 2100 m on the Ivory Coast-Ghana Ridge and Guyana margins [7,8].…”
Section: Introductionmentioning
confidence: 89%
“…However, these winnowing conditions can sometimes induce more or less marked stratigraphic gaps, which disrupt stratigraphic analysis. Despite their sometimes incomplete character on the scale of the last isotopic stages, the contouritic accumulations offer a glauconitic archive, often allowing the geochemical analysis of paleooceanic changes [7]. The vertical fluctuations in green-grain concentrations correspond to microsequences that are linked to the pulses of energy of the bottom water.…”
Section: Introductionmentioning
confidence: 99%
“…Another important property of Nd, which is particularly relevant to paleoceanographic studies, is that Nd hosted in solid phases is remarkably immobile during diagenesis (Banner, 2004; Luo et al., 2021; McLennan, 1989). Authigenic Nd in sediments is primarily stored in biogenic phosphates, banded‐iron formations, carbonates, Fe‐Mn nodules, and glauconites (e.g., Alexander et al., 2009; Bayon et al., 2004; Giresse et al., 2021; Zheng et al., 2013). While biogenic phosphates (conodonts, fish teeth) were initially regarded as the most suitable material for extraction of Nd signatures of seawater (e.g., Dopieralska et al., 2006, 2012; Grandjean et al., 1987; Holmden et al., 1996; Martin & Scher, 2004), in more recent years, carbonate fossils (benthic and planktonic foraminifera, aragonitic deep‐sea corals) and calcite micrite were used as archives of the past Nd isotope composition (e.g., Belka et al., 2021; Elmore et al., 2011; Haley et al., 2005; L. F. Robinson et al., 2014; Theiling et al., 2017; van de Flierdt et al., 2010; Wei et al., 2019).…”
Section: Introductionmentioning
confidence: 99%